Effects of circuit training and Yoga on biochemical and psychological responses to stress and cardiovascular markers: A randomized clinical trial with nursing and medical students in Southern Brazil - Haag F.B. (2024)
© 2024 Elsevier LtdA Randomized Controlled Trial involving 158 Brazilian medical and nursing students assessed one of three conditions over an 8-week period: 1) a circuit training protocol (CTG); 2) a yoga protocol (YG); or 3) no intervention (CG). The objective was to evaluate the effectiveness of circuit training and yoga protocols in reducing perceived mental stress and examining their effects on serum cortisol levels, as well as on traditional cardiovascular risk factors (CRFs), during an academic semester. Mental stress was measured using self-reported stress questionnaires. For the CTG, comparisons of pre- vs. post-intervention data indicated a reduction in self-reported stress levels on a Brazilian scale (p < 0.001) and an international scale (p < 0.05). Regarding CRFs, there was a reduction in waist circumference (WC) (p < 0.05), systolic blood pressure (SBP) (p < 0.05), and heart rate (HR) (p < 0.001). No changes were observed in diastolic blood pressure (DBP) (p = 0.211) and serum cortisol (SC) (p = 0.423). In the YG, pre- vs. post-intervention data indicated a reduction in self-reported stress levels on the ISSL (p < 0.001), in both resistance and exhaustion stress levels on the PSS scale (p < 0.001), and in SC levels (p < 0.001), WC (p < 0.05), and SBP (p < 0.05); however, HR and DBP did not change (p = 0.168 and p = 0.07, respectively) in this group. No changes were noted in any measures in the CG. The intervention protocols demonstrated that both CTG and YG can positively impact mental or biochemical stress responses, as well as CRFs.